Reducing Employee Turnover by Improving Trust in Organization Through Supervisory Support - Roslee, Azura; Effendi, Azura Abdullah (School of Social Sciences, USM, 2017)
This paper highlights the significance of organizational trust in the relationship between supervisory support and employee turnover. This review is imperative as an employee’s well-being encompasses many fundamental dimensions of employment, several of which can be significantly affected by an immediate supervisor. A survey of previous literature reveals perceived supervisor support associated with employee turnover intention. Previous studies also suggest that an employee’s trust in the organization should enhance retention, and found evidence that this variable had a clear negative relationship with organizational turnover rates. Additionally, in other studies, the quality of supervision was found to influence turnover intention. The current study proposes that trust in organization mediates the relationship between supervisory support and intention to turnover. The findings of this study will assist managers in building supportive job conditions needed to enhance employee trust in the organization, and researchers in further investigating the impact of trust in organization on employee turnover intentions.